STRUKTUR MODAL DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN YANG BERGABUNG DALAM INDEKS LQ-45 DENGAN RETURN SAHAM SEBAGAI VARIABEL INTERVENING PERIODE 2018-2021 - Meilinda, Silvi; Wahyuni, Ika; Pramitasari, Triska Dewi (Fakultas Ekonomi dan Bisnis, 2023)
The purpose of this study is to determine the effect of capital structure and dividend policy on company value through stock returns as an intervening variable in companies listed on the LQ-45 Index for the 2018-2021 periods. The populations in this study are all companies listed in the LQ-45 Index totaling 45 companies. The sampling technique in this study used purposive sampling so that 9 samples were obtained. Data analysis and hypothesis testing in this study using the Structural-Partial Least Square (SEM-PLS) method. The results of the hypothesis test for direct and indirect effects using the Smart PLS 3.0 application, the direct effect hypothesis test shows that capital structure and dividend policy have a negative but not significant effect on stock returns, capital structure has a negative but not significant effect on company value, dividend policy has a positive effect but not significant to company value, stock return has a positive and significant effect on company value. The results of the indirect effect test show that capital structure has a negative but not significant effect on firm value through stock returns. Dividend policy has a negative but not significant effect on company value through stock returns.